Law Enforcement and Justice: Perspective of Authority and Responsibility of the President towards the Judicial System - Ridlwan, Zulkarnain; Firmansyah, Ade Arif (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2020)
An independent judicial power is very important as one of the main characteristics of the rule of law, therefore its position must be maintained in Indonesia. The purpose of this paper confirms that any attempt to intervene in the authority of the Supreme Court and the Constitutional Court in the justice system, including intervention from the President, must be considered an unconstitutional act and violates the ideals of the Indonesian rule of law. A review of the President's position in the statutory regulations found the fact that there was still a gap in the infiltration of the President's power over judicial authority. Specifically in two cases, the first relates to the ambivalence of the prosecutor's position that is not as firm as the Police. Second, the constitutional judge selection model. The need to re-arrange the mechanism for selecting constitutional judges derived from the President's proposal so that it can be more aligned with efforts to distance the President's power from the power of the judiciary. In addition to the recommendations to the formers to reorganize the two potential infiltrations, this paper also recommends the institutionalization of public petitions based on Mark Tushnet's ideas about populist constitutional law. The existence of a public petition institution becomes a forum for gathering input and advice in law enforcement and justice. The opening of the President to accept public petitions makes it easier for the people to submit law enforcement issues which, in a sense of people's justice, must be addressed.